Novel Developments in Lung and Gut Microbiota and Their Cross-talk with the Development of Chronic Obstructive Pulmonary Disease - SHEN Junxi, ZHU Xing, CHEN Yunzhi, LI Wen (Zhongguo quanke yixue, 2023)
Chronic obstructive pulmonary disease (COPD) is a common chronic respiratory disease that greatly threatens human health. Studies have found that compared with the healthy population, the mucosal barrier function and immune homeostasis in COPD patients are impaired due to significantly changed composition and structure of both lung and gut microbiota, which further aggravate the disease progression. Taking measures to actively improve the microbial balance in lung and gut microbiota is very important for the prevention and delaying of the development of COPD. However, the summary and understanding of the role of lung and gut microbiota and their cross-talk mechanism in COPD still have much room for development. We reviewed the latest developments in the composition characteristics of lung and gut microbiota and the possible cross-talk mechanism between them in healthy people and COPD patients, as well as the prevention and treatment of COPD based on lung and gut microbiota and their cross-talk, providing new ideas for pathogenesis exploration, early diagnosis, prevention and treatment of COPD.